"Effectiveness of online recruitment system : evidence from augere wireless broadband Bangladesh limited (QUBEE)" - Haque, Nusrat (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2014.